INTERPRETATION, GOALS AND MAIN TASKS OF THE PERSONNEL POLICY OF THE ENTERPRISE - MAZUR, Galina; MAZUR, Dmytro; MAZUR, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the goals and main tasks of the company’s personnel policy. It has been established that the modern concept of the company’s personnel policy is based on a clear system of principles that determine the mandatory reasonableness, expediency and social responsibility. It is also determined that the personnel policy provides for orientation to certain labor markets, at the expense of which its tasks are implemented. that personnel policy is a system of views, principles and rules that regulate the activities of all personnel and each individual person. It can also be added that personnel policy is one of the most important areas of management activity of any organization. The essence of personnel policy is such work with personnel that corresponds to the development of the organization, that is, personnel policy is an integral part of the strategically oriented policy of the organization. The main goal of personnel policy is to create a personnel management system based mainly on economic incentives and social guarantees aimed at converging the interests of the employee and the organization, achieving high labor productivity, increasing production efficiency, and obtaining the best economic results by the organization. The tasks of the organization’s personnel policy should be related to determining the compliance of quantitative and qualitative characteristics of employees with job instructions, which, in turn, meet modern market requirements. Personnel policy is one of the most important tools of active influence on all processes that take place in the collective, in particular, on the development of the economy of our country, since the solution of many economic issues largely depends on the correct use of personnel. Work with personnel refers to the key moments of the activity of any enterprise, as an element of the state economy. Personnel policy should be aimed not only at creating favorable working conditions, but also at ensuring the possibility of advancement on the career ladder, creating confidence in the future.